Image, Mask and Persona in the Russian Poetry at the Turn of 21st Century - Matveeva, Victoria Valerjevna; Domanski, Yuri Victorovich; Skvortsov, Artem Eduardovich (Journal of History Culture and Art Research, 2017)
Poetry at the turn of 20-21st centuries is a heterogeneous and largely unexplored phenomenon. The works, in which the issues of contemporary Russian poetry development are considered systematically, are of fundamental importance. One of the important problems of this period is the tendency to a literary game - including image, mask nature and character in poetry. For all its obviousness, this problem was not studied conceptually. The purpose of this work is to examine the ways of image-making, masking and character in modern poetry and their interpretation from the point of view of genesis. The following conclusions were drawn after the study: 1) Masking and character in poetry are more often manifested in 1980s - 90s (and during an earlier period), whereas 2000s and subsequent years are marked by image-making. 2) The authors of the older and middle generation tend toward masking and character, while the younger, on the contrary, prefer image design (although exceptions are found in all three groups). 3) Masking and character in its origin are the phenomena of the late Soviet era. 4) Image making comes to the forefront during the last period when literature began to experience a serious pressure from the modern media environment, dictating new ways of interaction between a poet and an audience. The performed analysis of these trends determined the final conclusion: the propensity of modern authors to character and masking will continue to decrease, and the impact of image-making will be growing for some time until the change of the social-cultural paradigm from postmodern to another one.